Application of the Beneish M-Score Model in Detecting Financial Statement Fraud in Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange in 2019-2023 - Latifah Anjarini; Hanifah Puspita Sari; Ahmad Saifi Athoillah (JBS Nexus, 2025)
The high rate of fraud in Indonesia, especially in financial reports, is a serious concern because it causes large losses. This study aims to analyse the percentage level of transportation and logistics sector companies listed on the Indonesia Stock Exchange during the 2019- 2023 period which are classified into three categories, namely manipulators, grey companies and non-manipulators. This study uses a quantitative descriptive method with purposive sampling technique resulting in 20 companies as samples. The data used is secondary data obtained from annual financial reports and analyzed using eight Beneish M-Score ratios. The results showed fluctuations in the manipulator category with the highest percentage in 2020 at 35%. The grey company category was found at 5% in 2019 and 2021, and 10% in 2022, but not found in 2020 and 2023. Meanwhile, the non-manipulator category dominates with the highest proportion of 95% in 2023. The level of integrity of financial statements in the transport and logistics sector has not been consistent. Investors and creditors should be more aware of the potential manipulation of financial statements in order to avoid the risk of loss. Companies are expected to increase transparency and compliance with financial reporting standards to maintain stakeholder trust.